An investigation on scaling failure of heat exchanger in cooling water system of natural gas purification plant. Issue 5 (19th June 2022) - Jiang, Jingjing; Huang, Ganghua; Wang, Yanran; Fan, Rui
Abstract: In this study, a natural gas purification plant adopts open circulating water system, which cannot work properly and hinder the normal production of natural gas due to the problems such as scaling and blockage in the operation of heat exchanger device was reported. Qualities of the make‐up water and recirculating cooling water were evaluated by parameters such as hardness, alkalinity, pH, and conductivity. X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and optical microscope were employed to study the crystal structure, composition, and morphology of the scale deposits. The flow rate of the water in the tube bundle was calculated according to the design scale of these exchangers. The Langelier Saturation Index (LSI) was used to analyze the scale tendency of the cooling water system. The scale inhibition performance of the inhibitor was verified by static inhibition method. Results show that the scale mainly contains calcium carbonate, and the quality of circulating water is reasonably controlled with a proper range. However, there are three units sharing one cooling water system, of which the flow rate cannot be adjusted according to the actual heat load. The calculation results confirmed that the circulating water velocity in the tube bundle did not exceed 0.9 m/s. Although the scale inhibitor has a scale inhibition efficiency of more than 90% for the simulated circulating water at 80°C, the LSI analysis results showed that the high local temperature on the surface of the tube bundle caused by the low flow rate of water will increase the scaling tendency of the heat exchanger. Furthermore, the untimely injection of the inhibitor in the daily management and operation also greatly increased the risk of system scaling. This paper proves that the scaling of circulating water heat exchanger in the purification plant is mainly caused by device design and poor daily management. In order to prevent future failures, potential solutions and mitigation strategies were put forward.